Effectiveness of visual representations in promoting exact selection of continuity correction / Tuh Moi Hua... [et al.] - Moi Hua, Tuh; Liew, Chin Ying; Ahmad Bakri, Syah Runniza; Yee Hui, Robin Chang (Universiti Teknologi MARA, Negeri Sembilan, 2017)
The Square + Line method was formulated to enhance the understanding of students in cases involving Normal Approximation to either Binomial Distribution or Poisson Distribution. In these topics, usage of continuity correction factor is essential, specifically when we apply continuous function to approximate a discrete one. The simple steps of modifying (adding or subtracting 0.5) the discrete x-value are made complicated by the various interval situations. Through this approach, students can visualize the correct conversion for all the nine transformation cases. While it is possible that this method does not benefit quick learners, it nevertheless helps students who have difficulty with continuity knowledge retention. To measure the effectiveness of this method, students who took diploma program in computer science were given pre- and post-assessment before and after the learning session. The comparatively much higher post-test score indicates a significant improvement.